Failure of Monoiodoacetate to Induce Lameness in Dogs - Stobie, D.; Lipowitz, A. J.; Greer, Nancy L. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Intra-articular sodium monoiodoace-tate (MIA) has been shown to consistently induce a reproducible model of chronic arthritis in rats, chickens, guinea pigs, rabbits and horses. The purpose of this study was to determine if intra-articular injections of MIA would produce clinical signs of degenerative joint disease in dogs.Two different doses of MIA were injected into the stifle joints of normal dogs. Changes in limb function were evaluated by physical examination and force platform gait analysis. The dogs were evaluated weekly for three weeks, after which the MIA injections were repeated. They were again evaluated weekly for an additional two weeks.Significant changes in limb function were not found during any portion of the study as determined by physical examination of the injected joints and force platform gait analysis. Intra-articular MIA, at the doses used in this study, did not induce lameness nor clinical signs of degenerative joint disease.This study evaluated the potential of intra-articular injections of sodium monoiodoacetate (MIA) to produce degenerative joint disease in dogs. Changes in the injected joints and limb function were evaluated by physical examination and force platform gait analysis. Intraarticular MIA at the doses used in this study did not induce lameness nor clinical signs of degenerative joint disease in dogs.
Keywords: Induced arthritis